2000
DOI: 10.1034/j.1399-3003.2000.16f08.x
|View full text |Cite
|
Sign up to set email alerts
|

Breath isoprene during acute respiratory exacerbation in cystic fibrosis

Abstract: Patients with cystic fibrosis (CF) experience a combination of chronic systemic oxidative stress, generation of free radicals in the lungs due to a hyperimmune response and a diminished ability to scavenge free radicals secondary to malabsorption and increased consumption. The authors asked the question, "Does breath isoprene content reflect systemic oxidative stress?"The study involved 12 CF patients and 12 matched healthy controls. The patients were sampled during acute respiratory exacerbation (increased re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 26 publications
0
50
1
Order By: Relevance
“…Average values for acetone and dimethyl sulfide were comparable to that observed in healthy adults (displayed in Table 1) whilst average methanol and isoprene values in the study subjects were generally lower than that observed in the group of healthy adults (consistent with a previous study on children's breath (Taucher et al, 1997)). Previous reports have linked dimethyl sulfide and isoprene to cystic fibrosis and respiratory exacerbation (Barker et al, 2006;Kamboures et al 2005;McGrath et al, 2000). However, the present results indicate no significant difference between dimethyl sulfide and isoprene in the cystic fibrosis ( (Wang et al, 2006;Enderby et al, 2009).…”
Section: Direct Ptr-tof-ms Applied To Fingerprinting Breathcontrasting
confidence: 82%
“…Average values for acetone and dimethyl sulfide were comparable to that observed in healthy adults (displayed in Table 1) whilst average methanol and isoprene values in the study subjects were generally lower than that observed in the group of healthy adults (consistent with a previous study on children's breath (Taucher et al, 1997)). Previous reports have linked dimethyl sulfide and isoprene to cystic fibrosis and respiratory exacerbation (Barker et al, 2006;Kamboures et al 2005;McGrath et al, 2000). However, the present results indicate no significant difference between dimethyl sulfide and isoprene in the cystic fibrosis ( (Wang et al, 2006;Enderby et al, 2009).…”
Section: Direct Ptr-tof-ms Applied To Fingerprinting Breathcontrasting
confidence: 82%
“…Therefore, the collection of exhaled breath condensates (EBC) has been suggested to detect and monitor the course of inflammatory markers in CF and other airways diseases [147]. Volatile compounds such as hydrogen peroxide (H 2 O 2 ) [148], nitric oxide [149], 8-isoprostane [150] and isoprene [151] have been measured in EBC from CF and other patients. However, whether these markers of inflammation can be used to monitor anti-inflammatory therapy in CF is still questionable.…”
Section: Diagnosis and Monitoring Of Lung Inflammationmentioning
confidence: 99%
“…Studies have been developed using HS-SPME in order to establish the volatile composition of human exhaled breath [8] or for a specific type of disease, for example diabetes [14], lung cancer [15] and cystic fibrosis [16] or for chemical substances exposure monitoring [17]. Studies concerning non invasive monitoring of allergic airway inflammation have been made using exhaled nitric oxide [18] or breath condensate [19].…”
Section: Introductionmentioning
confidence: 99%